Airway strategy and ventilation rates in the pragmatic airway resuscitation trial. (July 2022) - Wang, Henry E.; Jaureguibeitia, Xabier; Aramendi, Elisabete; Nichol, Graham; Aufderheide, Tom; Daya, Mohamud R.; Hansen, Matthew; Nassal, Michelle; Panchal, Ashish R.; Nikolla, Dhimitri A.; Alonso, Erik; Carlson, Jestin; et al.
Abstract: Background: We sought to describe ventilation rates during out-of-hospital cardiac arrest (OHCA) resuscitation and their associations with airway management strategy and outcomes. Methods: We analyzed continuous end-tidal carbon dioxide capnography data from adult OHCA enrolled in the Pragmatic Airway Resuscitation Trial (PART). Using automated signal processing techniques, we determined continuous ventilation rates for consecutive 10-second epochs after airway insertion. We defined hypoventilation as a ventilation rate < 6 breaths/min. We defined hyperventilation as a ventilation rate > 12 breaths/min. We compared differences in total and percentage post-airway hyper- and hypoventilation between airway interventions (laryngeal tube (LT) vs. endotracheal intubation (ETI)). We also determined associations between hypo-/hyperventilation and OHCA outcomes (ROSC, 72-hour survival, hospital survival, hospital survival with favorable neurologic status). Results: Adequate post-airway capnography were available for 1, 010 (LT n = 714, ETI n = 296) of 3, 004 patients. Median ventilation rates were: LT 8.0 (IQR 6.5–9.6) breaths/min, ETI 7.9 (6.5–9.7) breaths/min. Total duration and percentage of post-airway time with hypoventilation were similar between LT and ETI: median 1.8 vs. 1.7 minutes, p = 0.94; median 10.5% vs. 11.5%, p = 0.60. Total duration and percentage of post-airway time with hyperventilation were similar between LT and ETI: median 0.4 vs. 0.4 minutes, p = 0.91; median 2.1% vs. 1.9%, p = 0.99. Hypo- and hyperventilation exhibited limited associations with OHCA outcomes. Conclusion: In the PART Trial, EMS personnel delivered post-airway ventilations at rates satisfying international guidelines, with only limited hypo- or hyperventilation. Hypo- and hyperventilation durations did not differ between airway management strategy and exhibited uncertain associations with OCHA outcomes.